Authentic Assessment in Online Learning During The Covid-19 Pandemic - Masnurul Sholihah (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the ability of subject teachers in making an authentic instrument after studying the material about authentic assessment. The variables of this study include authentic instruments made by each subject teacher to be analyzed descriptively using a simple analytical rubric. The conclusion of this research is that after studying the material on authentic assessment, all subject teachers can make one or more authentic assessment instruments with the criteria for making the results of which the average is very good.